A Qualitative Approach to Educational Research: Language Courses in English Studies - Arnó-Macià, Elisabet (HERMES - Journal of Language and Communication in Business, 2010)
This paper reports on a qualitative study focusing on the role of language awareness in university language courses that form part of English Studies (ES). Language constitutes the subject matter of students’ discipline and the ES degree is the initial training for future language teachers and other language-related professionals. Therefore, the models and views of language presented at university will inﬂuence graduates’ future professional practice. This study focuses on how language awareness is approached in language classes and on lecturers’ and students’ views of language and learning. This article will discuss how a qualitative methodology was used to ﬁnd out about participants’ practices and views on language and learning, through immersion in a university language course over a term. Using a descriptive-interpretive paradigm, data were gathered from classroom observations and interviews, and analysed through the combination of ethnography and discourse analysis. This paper presents the methodological underpinnings of this research, decisions on the selection of data, interaction with participants, researcher’s stance, and warranting. Through the understanding of participants’ practices and views, this study provides a picture of how language awareness is approached in a university language course.